The Effect Of Information Search Toward Students’ Reading Comprehention - Edi Firman; M. Asrul Hasby (Lembaga Penelitian dan Pendidikan Mandala, 2020)
This study was intended to analyze whether Information has significant effect toward students’ reading comprehension. The method of this research was quantitative approach and applied pre-experimental design by using pre-test and post-test. The population of this research was whole of the first-grade students of SMKS DARUL QUR’AN BENGKEL which was consisted of one class with the total number of populations was 29 students in X TKJ Group Class as population sample. The class was treated by using Students Information Search. The instrument used in this research was reading test, in form of multiple choices test which was consisted of 25 items. The data was analyzed using t-test. The result of the data analysis indicated that Information Search has significant effect towards students’ reading comprehension. The result of statistical computation confirmed that the result of sig. two-tailed is differ from the value significant level (0.000 ≠ 0.05). the researcher also found the result of t-table was 2.061 lower then t-test 12.679. This result indicated that Alternative Hypothesis was accepted and Null Hypothesis was rejected, therefore it can be concluded that there is significant effect of Information Search towards students’ reading comprehension.